Strengthening MSME Human Resources in Cianjur Through Knowledge Management Market to Boost Creativity and Sales - Syafei, M Yani; Narimawati, Umi; Triyanto, Dedi; Hermawan, Budi (MOVE: Journal of Community Service and Engagement, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are one of the most significant contributors to Indonesia's economy. In Cianjur Regency, West Java, MSMEs serve as the backbone of the local economy, offering a wide range of products such as handicrafts, traditional foods, and fashion items. However, MSME actors in this region often face significant challenges in terms of business management, limited knowledge of modern strategies, and restricted access to technology and modern markets. To address these issues, the Knowledge Management Market program was introduced as part of the Community Service Week in Cianjur. This initiative aims to strengthen the human resources (HR) of MSMEs through a knowledge-based approach to enhance creativity and sales.